White Privilege, White Poverty: Reckoning with Class and Race in America - Blacksher, Erika (The Hastings Center report, 2021)
This essay argues that a failure to think and talk critically and candidly about White privilege and White poverty is a key threat to the United States of America's precarious democracy. Whiteness frames one of America's most pressing collective challenges—the poor state of the nation's health, which lags behind other wealthy nations and is marred by deep and entrenched class- and race-based inequities. The broadscale remedies experts recommend demand what is in short supply: trust in evidence, experts, government, and one another. The authors’ prescription is threefold, beginning with a call for intersectional health studies and reports that avoid one-dimensional misrepresentations of widespread health problems as simply Black or White problems. Second, there is the need for a “critical consciousness” about race and class. Lastly, the essay calls for widescale opportunities for Americans to engage in cross-racial and cross-class democratic conversations about their struggles and aspirations in search of common ground.